DISCOVERY OF A NEW POPULATION OF CYRTODACTYLUS SONI LE, NGUYEN, LE & ZIEGLER, 2016 FROM HA NAM PROVINCE - Quang Vinh, Luu; Thanh Tung, Nguyen; Thanh Hai, Dong (Journal of Forestry Science and Technology, 2018)
A new population of the Son’s Bent-toed Gecko (Cyrtodactylus soni) is reported for the first time from Ha Nam province, in the North of Vietnam, based on six specimens collected in May 2017 on the karst cliffs in the secondary karst forest of Thanh Son commune, Kim Bang district. Morphological characters of these specimens are mostly matched with the original description of Le et al. (2016), such as supralabials 11 - 12; infralabials 9 - 10; 41 longitudinal rows at midbody. In addition, specimens from Ha Nam province is different from the original description by having fewer femoral pore counts in females (0 - 6 pitted scales versus 6 - 8 pitted scales in the type series). Two female specimens VNUF RHN.2017.06 and VNUF RHN.2017.07 are different in color pattern from the original description (ground color yellowish-white versus brownish-grey, distinct darker transverse bands), and dorsal head of two specimens also with less dark markings. The population of this species in Ha Nam is threatened by habitat loss through quarrying of limestone and its locality is close to the But Son cement factory. Therefore, assessment of distribution and threats to the population in the study area is crucially needed to provide scientific data for conservation measures.